2011
DOI: 10.1039/c1nr10940e
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption and emission of nitrogen-doped silicon nanocrystals

Abstract: Silicon nanocrystals (Si NCs) may be both unintentionally and intentionally doped with nitrogen (N) during their synthesis and processing. Since the importance of Si NCs largely originates from their remarkable optical properties, it is critical to understand the effect of N doping on the optical behavior of Si NCs. On the basis of theoretical calculations, we show that the doping of Si NCs with N most likely leads to the formation of paired interstitial N at the NC surface, which causes both the optical absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…As the excitation wavelength increases from 325 nm to 400 nm, shape line of NIR emission spectra show no any recognized change and emission peaks are pinned at ~920 nm. It is worth noticing that the behavior of PL in our case is identical to that of surface states related PL which peak position is independent of the excitation wavelengths because of the narrow distribution of surface localized states [28]. Therefore, in our case the 1.35 eV NIR emission is suggested from the radiative recombination via surface states of Si nanocrystals.…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…As the excitation wavelength increases from 325 nm to 400 nm, shape line of NIR emission spectra show no any recognized change and emission peaks are pinned at ~920 nm. It is worth noticing that the behavior of PL in our case is identical to that of surface states related PL which peak position is independent of the excitation wavelengths because of the narrow distribution of surface localized states [28]. Therefore, in our case the 1.35 eV NIR emission is suggested from the radiative recombination via surface states of Si nanocrystals.…”
Section: Methodssupporting
confidence: 60%
“…5(a), it is noticed that the 390 nm PLE band redshifts in comparison to that observed in Si nanostructures with complete H passivation. Pi et al have found that paired interstitial N or doubly bonded O at the surface of Si nanocrystals would reduce the energy of the highest occupied molecular orbital (HOMO) and the lowest occupied molecular orbital (LUMO) of Si nanocrystals at excited state [28]. Thus, combining with the FTIR and XPS spectra analyses mentioned above, the redshift of the 390 nm PLE band can be ascribed to the N-Si-O at the NCs surface.…”
Section: Methodsmentioning
confidence: 98%
“…Annealing in N 2 atmosphere has been shown to result in a submonolayer nitrogen coverage of the Si-nc, which reduces on the one hand the polarity at the Si-nc to matrix interface, thereby increasing the Si-nc bandgap, and on the other hand to saturate dangling bonds at the Si-nc interface, thereby improving PL yield. 24,25 As both RTP and furnace annealing treatments were performed under N 2 atmosphere, these N-related effects were active for all of our samples. From a comparison of Si-nc PL spectra after RTA and after Er 3þ implantation and the corresponding furnace anneal, 26 no relative PL peak blueshift could be found for annealing temperatures up to 950 C. This indicates rather complete N 2 diffusion already during the initial RTA treatment and no further specific Nrelated changes during the longer furnace anneal.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…2008年, Macedo等人 [26] [29] ; 理论计算了掺杂的B, P在硅量子点中可 能存在的位置, 并对其引起的红外波段的吸收及对硅 量子点发光性能的影响进行了研究 [30,31] ; 结合密度泛 函理论和实验, 研究了硅烷化、烷化、烷氧基化及胺 化这4种表面改性对氯钝化硅量子点电子结构和光学 性能的影响 [32~34] . 结果表明, 胺化反应引发的表面化学 效应能够显著降低硅量子点的激发能和发射能, 并对 硅量子点的分子轨道能级产生影响.…”
Section: 硅量子点发光unclassified